Thermoplastic resin composition and molded product of the same

JP2023158352A5Inactive Publication Date: 2025-01-10IDEMITSU KOSAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022068138
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-18
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Thermoplastic resins used as matrices in fiber-reinforced plastics face challenges with mechanical strength and moisture and heat resistance, limiting their application in demanding environments.

Method used

A thermoplastic resin composition comprising three types of resins with a co-continuous structure morphology, where each phase has a specific composition and compatibility, including a sea-island structure, to enhance mechanical strength and heat and humidity resistance.

Benefits of technology

The composition achieves high mechanical strength and excellent heat and humidity resistance, maintaining strength retention even after prolonged moist heat exposure, suitable for diverse applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a thermoplastic resin composition which has high mechanical strength and excellent moist heat resistance, and a molded product of the same.SOLUTION: A thermoplastic resin composition contains a thermoplastic resin (A), a thermoplastic resin (B), and a thermoplastic resin (C), and has a morphology of a co-continuous structure, wherein the first phase of the co-continuous structure is mainly composed of the thermoplastic resin (A), the second phase of the co-continuous structure is mainly composed of a mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C), in the first phase, the mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C) is dispersed in the thermoplastic resin (A), and in the second phase, the thermoplastic resin (A) is dispersed in the mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to thermoplastic resin compositions and molded articles thereof. [Background technology]

[0002] In recent years, particularly in the automotive sector, improving fuel efficiency by reducing weight has been a focus of research. For example, there is a growing movement to replace conventional metal structural components with fiber-reinforced plastics, and fiber-reinforced plastics with superior strength are in demand.

[0003] Reinforced fiber composite materials with a thermoplastic resin matrix (for example, carbon fiber reinforced thermoplastic resin, sometimes abbreviated as CFRTP) are being investigated for practical use due to their advantages of ease of molding and processing and ease of recycling (Patent Documents 1 and 2). [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2018-145245 [Patent Document 2] International Public Gazette 2020 / 174748 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] When thermoplastic resin is used as the matrix, as mentioned above, it has advantages such as ease of molding and ease of recycling. However, there were challenges in terms of mechanical strength and resistance to moisture and heat.

[0006] The object of the present invention is to provide a thermoplastic resin composition and a molded article thereof that have high mechanical strength and excellent resistance to moisture and heat. [Means for solving the problem]

[0007] In view of the above problems, the inventors investigated the morphology of thermoplastic resin compositions. As a result, they found that when three types of thermoplastic resins are used in combination to exhibit a co-continuous morphology, and when each phase constituting the co-continuous structure has a sea-island morphology, a thermoplastic resin composition with high mechanical strength and resistance to moisture and heat is obtained, thus completing the present invention.

[0008] According to the present invention, the following thermoplastic resin compositions and the like are provided. 1. Includes thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C), It has a co-continuous structure morphology, The first phase of the co-continuous structure mainly consists of the thermoplastic resin (A), and the second phase of the co-continuous structure mainly consists of a mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C). In the first phase, a mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C) is dispersed in the thermoplastic resin (A). A thermoplastic resin composition in which, in the second phase, the thermoplastic resin (A) is dispersed in a mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C). 2. The average diameter of the mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C) present in the first phase is 500 nm or less. The thermoplastic resin composition according to claim 1, wherein the average diameter of the thermoplastic resin (A) present in the second phase is 500 nm or less. 3. The thermoplastic resin composition according to 1 or 2, wherein the thermoplastic resin (A) and the thermoplastic resin (C) have polar functional groups, and the thermoplastic resin (B) and the thermoplastic resin (C) are perfectly miscible. 4. The thermoplastic resin composition according to 3, wherein the polar functional groups of the thermoplastic resin (A) and the thermoplastic resin (C) are carboxyl groups or amino groups. 5. The thermoplastic resin composition according to any one of 1 to 4, wherein the thermoplastic resin (A) and the thermoplastic resin (B) are crystalline resins. 6. The thermoplastic resin composition according to any one of 1 to 5, wherein the thermoplastic resin (C) is a polyarylene ether. 7. The thermoplastic resin composition according to any one of 1 to 6, wherein the thermoplastic resin (B) is syndiotactic polystyrene. 8. The thermoplastic resin composition according to any one of 1 to 7, wherein the mass ratio of the thermoplastic resin (A) to the total of the thermoplastic resin (B) and the thermoplastic resin (C) ((A):((B)+(C))) is 40:60 to 60:40. 9. The thermoplastic resin composition according to any one of 1 to 8, wherein the thermoplastic resin (C) is 3 to 15 parts by mass with respect to 100 parts by mass of the total ((A)+(B)+(C)) of the thermoplastic resin (A), the thermoplastic resin (B), and the thermoplastic resin (C). 10. The thermoplastic resin composition according to any one of 1 to 9, further comprising a reinforcing fiber (D). 11. The thermoplastic resin composition according to 10, wherein the reinforcing fiber (D) is at least one selected from glass fiber and carbon fiber. 12. The thermoplastic resin composition according to 10 or 11, wherein the surface of the reinforcing fiber (D) is coated with the first phase. 13. A molded article comprising the thermoplastic resin composition according to any one of 1 to 9. 14 A molded article comprising the thermoplastic resin composition according to any one of 10 to 12. 15. The molded article according to 14, wherein the strength retention rate after heat and humidity treatment at 80°C / 95%RH for 500 hours represented by the following formula (I) is 80% or more.

Number

Advantages of the Invention

[0009] According to the present invention, it is possible to provide a thermoplastic resin composition having high mechanical strength and excellent heat and humidity resistance, and a molded article thereof.

Brief Description of the Drawings

[0010] <000009 / >It is a cross-sectional scanning electron microscope (SEM) image of the thermoplastic resin composition obtained in Example 1. [Figure 2] It is an SEM image of the thermoplastic resin composition obtained in Comparative Example 1. [Figure 3] It is an enlarged image of the SEM image (Example 1) in FIG. 1. [Figure 4] It is an enlarged image of the SEM image (Comparative Example 1) in FIG. 2. [Figure 5] It is a cross-sectional SEM image of carbon fibers in the thermoplastic resin composition obtained in Example 1. [Figure 6] It is a cross-sectional SEM image of carbon fibers in the thermoplastic resin composition obtained in Comparative Example 1.

Mode for Carrying Out the Invention

[0011] Hereinafter, the thermoplastic resin composition and its molded body of the present invention will be described in detail. In this specification, the specified provisions that are considered preferable can be arbitrarily adopted, and combinations of preferable ones are more preferable. In this specification, the description of "XX to YY" means "XX or more and YY or less".

[0012] The thermoplastic resin composition according to the first embodiment of the present invention contains thermoplastic resins (A), (B), and (C) that are different from each other. And it is characterized in that the following morphologies A and B are observed by a scanning electron microscope (SEM) of the cross section. [[ID=二十八]] Morphology A: It is a co-continuous structure. The first phase of the co-continuous structure mainly consists of thermoplastic resin (A), and the second phase of the co-continuous structure mainly consists of a mixed phase of thermoplastic resins (B) and (C). Morphology B: In the enlarged observation of the first phase, a mixed phase of thermoplastic resins (B) and (C) is dispersed in thermoplastic resin (A) (sea-island structure). In the enlarged observation of the second phase, thermoplastic resin (A) is dispersed in the mixed phase of thermoplastic resins (B) and (C) (sea-island structure).

[0013] Here, a co-continuous structure refers to a structure in which multiple components are mixed together while each forming a continuous phase. A sea-island structure refers to a structure in which, among multiple components, the components that form a continuous phase (matrix) are dispersed in a particulate (island-like) manner. For information on co-continuous structures and sea-island structures, see, for example, "Basic Polymer Science One Point 7, Structure I: Polymer Alloys, The Society of Polymer Science, Japan, Kyoritsu Shuppan Co., Ltd., p. 22."

[0014] In a co-continuous structure, the first phase and the second phase are three-dimensionally continuous, forming non-spherical and periodic phases that are mixed with each other. In this embodiment, the first phase mainly consists of a thermoplastic resin (A), and the second phase of the co-continuous structure mainly consists of a mixed phase of thermoplastic resin (B) and thermoplastic resin (C).

[0015] Morphology A is observed, for example, by taking an SEM image (photograph) of a cross-section of a thermoplastic resin composition polished for SEM observation at a magnification of approximately 5,000 to 15,000 times. Furthermore, the statement that the first phase mainly consists of thermoplastic resin (A) means that the area of ​​the same color (e.g., white) in the continuous phase of the first phase in the SEM image is 80% or more. The area of ​​the same color may be 90% or more. The statement that the second phase mainly consists of a mixed phase of thermoplastic resin (B) and thermoplastic resin (C) means that the area of ​​the same color (e.g., black) in the continuous phase of the second phase in the SEM image is 80% or more. The area of ​​the same color may be 90% or more.

[0016] In a sea-island structure, island-like phases are dispersed within a matrix (sea). In this embodiment, magnified observation of the first phase shows that a mixed phase of thermoplastic resin (B) and thermoplastic resin (C) is dispersed in thermoplastic resin (A) (sea-island structure), and magnified observation of the second phase shows that thermoplastic resin (A) is dispersed in the mixed phase of thermoplastic resin (B) and thermoplastic resin (C).

[0017] Magnified observation of morphology B is performed, for example, by taking an SEM image (photograph) of a cross-section of a thermoplastic resin composition polished for SEM observation at a magnification of approximately 25,000 to 35,000 times.

[0018] In this embodiment, when the cross-section of the thermoplastic resin composition is observed at a relatively low magnification, a co-continuous structure is observed, and when observed at a high magnification, a sea-island structure is observed within each phase constituting the co-continuous structure. Having such a morphology results in a thermoplastic resin composition with high mechanical strength and resistance to moisture and heat when molded into an article.

[0019] The above morphology can be achieved by melt-kneading a mixture containing thermoplastic resins (A) to (C). During mixing, thermoplastic resins (A) to (C) may be in powder form or pellet form. Alternatively, for example, thermoplastic resin (B) and thermoplastic resin (C) may be melt-kneaded beforehand, and then thermoplastic resin (A) and the mixture of thermoplastic resins (B) and (C) may be melt-kneaded together. Furthermore, as will be described later, known fillers and additives may be added to the thermoplastic resin composition of the present invention and melt-kneaded together to impart various functions to the molded article or improve its properties. As long as the objective of the present invention is not impaired, known additives may be added in small proportions.

[0020] Known methods can be used for melt mixing. Examples include single-screw mixers (mixers are sometimes called extruders), multi-screw mixers with two or more shafts, continuous mixers such as mixing rolls or calender rolls, or known mixers such as pressure kneaders and Banbury mixers. Among these, twin-screw mixers are preferred.

[0021] The L / D (effective barrel length / inner barrel diameter) of the extruder is preferably 20 to 60, and more preferably 30 to 50. The screw configuration is not particularly limited, but it is preferable to provide first to third kneading zones. For example, it is preferable to provide kneading zones upstream, midstream, and downstream with respect to the flow direction of the raw material. The configuration of the extruder is not particularly limited, but it is preferable to provide, for example, first to third vacuum vents. For example, it is preferable to provide the first vacuum vent behind the midstream kneading zone with respect to the raw material flow direction, and the second vacuum vent behind the downstream kneading zone.

[0022] The screw rotation speed is not particularly limited, but 100 to 500 rpm is preferred, and 200 to 400 rpm is more preferred from the viewpoint of controlling morphology and shear heat generation. The set temperature of the extruder is not particularly limited, but it is preferably +10°C to +150°C above the higher of the melting point or glass transition point of the thermoplastic resin used. From the viewpoint of suppressing thermal decomposition of the thermoplastic resin and controlling its morphology, it is more preferably +20°C to +100°C. Here, when two or more types of thermoplastic resins are used, the melting point or glass transition point of the resin with the highest melting point or glass transition point among the resins used is used as the reference.

[0023] The method of supplying raw materials is not particularly limited, but it is preferable to supply them from the first to third raw material supply ports. For example, it is preferable to dry blend the raw materials containing thermoplastic resin in the direction of raw material flow and supply them from the first raw material supply port upstream. When reinforcing fibers are added as fillers, it is preferable to supply them from the second raw material supply port located between the midstream and downstream.

[0024] The morphology of the present invention can be expressed by adjusting the fluidity of thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C). Fluidity can be measured, for example, by performing MFR measurement.

[0025] In morphology B (sea-island structure), it is preferable that the average diameter of the mixed phase (island portion) of thermoplastic resin (B) and thermoplastic resin (C) present in the first phase is 500 nm or less. Furthermore, it is preferable that the average diameter of the thermoplastic resin (A) (island portion) present in the second phase is 500 nm or less. This allows each resin to play a complementary role, resulting in excellent mechanical properties. The average diameter of the island portion is preferably 400 nm or less, and more preferably 300 nm or less. There is no specific lower limit for the average diameter of the island portion, but it is usually around 50 nm.

[0026] The average diameter can be measured by observing the morphology of the cross-section of the molded resin product using an optical microscope, SEM (scanning electron microscope), TEM (transmission electron microscope), etc. Specifically, for example, when observing using an SEM analyzer, the core portion of the molded product cross-section (excluding the surface layer less than 20 μm deep, the central part of the cross-section, and the cross-section parallel to the flow direction of the resin composition) can be observed at a magnification of 25,000 to 35,000 times under an accelerating voltage of 15 kV. From the observed image, 0.20 μm 2 For island components with the following areas, the equivalent diameter obtained by converting them to circles with the same area is defined as the particle diameter and is defined as the island component diameter. The average diameter of the island portion is calculated by arithmetic mean from the results of 100 island component diameters observed in 10 similarly captured, non-overlapping observation images.

[0027] In one embodiment, thermoplastic resin (A) and thermoplastic resin (C) have polar functional groups. This improves the interfacial strength between thermoplastic resin (A) and thermoplastic resin (C) and allows for the refinement of the morphological size. Examples of polar functional groups include carboxyl groups, amino groups, hydroxyl groups, halogen groups, epoxy groups, sulfonic acid groups, imide groups, and isocyanate groups.

[0028] In one embodiment, thermoplastic resin (A) and thermoplastic resin (B) are crystalline resins. This makes it possible to impart heat resistance, water resistance, and chemical resistance. The components of the thermoplastic resin composition of this embodiment will be described below.

[0029] <Thermoplastic resin (A)> The thermoplastic resin (A) mainly forms the first phase of the co-continuous structure. Thermoplastic resin (A) is not particularly limited as long as it is a resin that is not compatible with thermoplastic resin (B) and thermoplastic resin (C). Specifically, thermoplastic resin (A) can be polyamide resin, acrylic resin, polyphenylene sulfide resin, polyvinyl chloride resin, polyolefin, polyacetal resin, polycarbonate resin, polyurethane, polybutylene terephthalate, acrylonitrile butadiene styrene (ABS) resin, phenoxy resin, polysulfone, polyethersulfone, polyether ketone, polyether ether ketone, aromatic polyester, etc. Among these, polyamide resin is preferred.

[0030] As the polyamide, known polyamides can be used. Examples of polyamides include polyamide-4, polyamide-6, polyamide-6, 6, polyamide-3, 4, polyamide-12, polyamide-11, polyamide-4, 10, polyamide-6, 10, polyamide-4T, polyamide-6T, polyamide-9T, polyamide-10T, and polyamides obtained from adipic acid and m-xylylenediamine. Among these, polyamide-6, polyamide-6, 6, and polyamide-6, 10 are preferred.

[0031] In the thermoplastic resin composition of the present invention, the amount of thermoplastic resin (A) blended with thermoplastic resin (A) is preferably 40 to 60 parts by mass per 100 parts by mass of the total of thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C). More preferably, it is 45 to 55 parts by mass.

[0032] <Thermoplastic resin (B)> Thermoplastic resin (B) primarily forms a second phase of the thermoplastic resin composition by being compatible with thermoplastic resin (C), which is described in detail below. The thermoplastic resin (B) is not particularly limited as long as it is compatible with the thermoplastic resin (C). Specifically, examples include acrylic resin, polyphenylene sulfide resin, polyvinyl chloride resin, polystyrene resin, polyolefin, polyacetal resin, polycarbonate resin, polyurethane, polybutylene terephthalate, acrylonitrile butadiene styrene (ABS) resin, phenoxy resin, polysulfone, polyethersulfone, polyether ketone, polyether ether ketone, aromatic polyester, etc. Among these, polystyrene resin is preferred.

[0033] Polystyrene resins are not particularly limited, but examples include homopolymers of styrene compounds, copolymers of two or more styrene compounds, and rubber-modified polystyrene resins (high-impact polystyrene) in which rubbery polymers are dispersed in particulate form within a matrix composed of polymers of styrene compounds. Examples of styrene compounds used as raw materials include styrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, α-methylstyrene, ethylstyrene, α-methyl-p-methylstyrene, 2,4-dimethylstyrene, monochlorostyrene, and p-tert-butylstyrene.

[0034] The polystyrene resin may be a copolymer obtained by using two or more styrene compounds in combination, but polystyrene obtained by polymerization using styrene alone is preferred. Examples include polystyrenes having a stereoregular structure such as atactic polystyrene, isotactic polystyrene, and syndiotactic polystyrene. Among these, syndiotactic polystyrene is preferred as the thermoplastic resin (B) contained in the resin composition of the present invention.

[0035] Syndiotactic polystyrene refers to a styrene-based resin (hereinafter sometimes abbreviated as SPS) that has a highly syndiotactic structure. In this specification, "syndiotactic" means that there is a high proportion of phenyl rings in adjacent styrene units that are alternately arranged (hereinafter referred to as syndiotacticity) with respect to the plane formed by the main chain of the polymer block. Tacticity is determined by nuclear magnetic resonance spectroscopy using isotopic carbon. 13 Quantitative identification is possible by 13C-NMR spectroscopy. 13 1C-NMR allows for the quantitative determination of the relative abundance of multiple consecutive constituent units, such as a dyad (two consecutive monomer units), a triad (three consecutive monomer units), and a pentad (five consecutive monomer units).

[0036] "Styrene-based resins having a highly syndiotactic structure" means polystyrene, poly(hydrocarbon-substituted styrene), poly(halogenated styrene), poly(halogenated alkyl styrene), poly(alkoxystyrene), poly(vinyl benzoate ester), hydrogenated polymers or mixtures thereof, or copolymers mainly composed of these, having syndiotacticity of typically 75 mol% or more, preferably 85 mol% or more, in the racemic diad(r), or typically 30 mol% or more, preferably 50 mol% or more, in the racemic pentad(rrrr).

[0037] Examples of poly(hydrocarbon-substituted styrene) include poly(methylstyrene), poly(ethylstyrene), poly(isopropylstyrene), poly(tert-butylstyrene), poly(phenyl)styrene, poly(vinylnaphthalene), and poly(vinylstyrene). Examples of poly(halogenated styrene) include poly(chlorostyrene), poly(bromostyrene), and poly(fluorostyrene), and examples of poly(halogenated alkylstyrene) include poly(chloromethylstyrene). Examples of poly(alkoxystyrene) include poly(methoxystyrene) and poly(ethoxystyrene).

[0038] Among the polystyrene resins mentioned above, particularly preferred examples include polystyrene, poly(p-methylstyrene), poly(m-methylstyrene), poly(p-tert-butylstyrene), poly(p-chlorostyrene), poly(m-chlorostyrene), and poly(p-fluorostyrene). Furthermore, examples include copolymers of styrene and p-methylstyrene, copolymers of styrene and p-tert-butylstyrene, and copolymers of styrene and divinylbenzene.

[0039] There are no particular restrictions on the molecular weight of the above syndiotactic polystyrene, but from the viewpoint of the fluidity of the resin during molding and the mechanical properties of the resulting molded article, a weight-average molecular weight of 1 × 10⁻⁶ is desirable. 4 The above 1 x 10 6 Preferably, the weight-average molecular weight is 1 × 10⁻¹⁰. 4 If the above is achieved, a molded article with sufficient mechanical properties can be obtained. On the other hand, if the weight-average molecular weight is 1 × 10 6 The following conditions ensure that there are no problems with the fluidity of the resin during molding.

[0040] When the melt flow rate (MFR) is measured under conditions of 300°C and a load of 1.2 kg, it is preferably 2 g / 10 min or more, more preferably 4 g / 10 min or more, and also preferably 50 g / 10 min or less, more preferably 35 g / 10 min or less. If the MFR value of SPS is 2 g / 10 min or more, there are no problems with the fluidity of the resin during molding, and if it is 50 g / 10 min or less, a molded product with sufficient strength can be obtained.

[0041] The amount of thermoplastic resin (B) blended is preferably 25 to 57 parts by mass per 100 parts by mass of the total of thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C). More preferably, it is 40 to 50 parts by mass.

[0042] It is preferable that the thermoplastic resin (B) is perfectly miscible with the thermoplastic resin (C) described later. "Perfectly miscible" means that the glass transition temperature of the mixed resin of thermoplastic resin (B) and thermoplastic resin (C) is a single temperature. A single glass transition temperature means that when the glass transition temperature of the mixed resin is measured using a differential scanning calorimetry system at a heating rate of 10°C / min in accordance with JIS K-7121, only one peak indicating the glass transition temperature appears.

[0043] <Thermoplastic resin (C)> Thermoplastic resin (C) is mainly compatible with the above-mentioned thermoplastic resin (B) to form a second phase of the thermoplastic resin composition. The thermoplastic resin (C) is not particularly limited as long as it is a resin that is compatible with the thermoplastic resin (B). For example, polyarylene ether can be used. From the viewpoint of compatibility with thermoplastic resin (B), polyarylene ether is preferred, and polyarylene ether modified with functional groups is more preferred. Polyarylene ethers modified with functional groups can be obtained by reacting polyarylene ethers with a modifying agent.

[0044] The polyarylene ether used as a raw material for functionally modified polyarylene ethers is not particularly limited. For example, poly(2,3-dimethyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-chloromethyl-1,4-phenylene ether), poly(2-methyl-6-hydroxyethyl-1,4-phenylene ether), poly(2-methyl-6-n-butyl-1,4-phenylene ether), poly(2-ethyl-6-isopropyl-1,4-phenylene ether), poly(2-ethyl-6-n-propyl-1,4-phenylene ether), poly(2,3,6-trimethyl-1,4-phenylene ether), poly[2-(4'-methylphenyl)-1,4-phenylene ether], poly(2-phenyl-1,4-phenylene ether), poly(2-chloro-1,4-phenylene ether), poly( Examples include poly(2-methyl-1,4-phenylene ether), poly(2-chloro-6-ethyl-1,4-phenylene ether), poly(2-chloro-6-bromo-1,4-phenylene ether), poly(2,6-di-n-propyl-1,4-phenylene ether), poly(2-methyl-6-isopropyl-1,4-phenylene ether), poly(2-chloro-6-methyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2,6-dibromo-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), and poly(2,6-dimethyl-1,4-phenylene ether). Furthermore, polymers and copolymers described in the specifications of U.S. Patents No. 3,306,874, No. 3,306,875, No. 3,257,357, and No. 3,257,358 are also suitable. In addition, for example, graft copolymers and block copolymers of vinyl aromatic compounds such as polystyrene and the aforementioned polyphenylene ethers are also mentioned. Among these, poly(2,6-dimethyl-1,4-phenylene ether) is particularly preferred.

[0045] There are no particular restrictions on the degree of polymerization of the polyarylene ether; it can be appropriately selected according to the intended use, and is usually selected from the range of 60 to 400. If the degree of polymerization is 60 or higher, as will be described in detail later, the strength of the resin composition containing the functionally modified polyarylene ether (A) can be improved. If the degree of polymerization is 400 or lower, good moldability can be maintained.

[0046] Examples of modifying agents for the above-mentioned polyarylene ether include acid modifying agents, amino group-containing modifying agents, phosphorus compounds, hydroxyl group-containing modifying agents, halogen-containing modifying agents, epoxy group-containing modifying agents, and unsaturated hydrocarbon group-containing modifying agents. Examples of acid modifying agents include dicarboxylic acids and their derivatives.

[0047] Examples of dicarboxylic acids used as denaturing agents include maleic anhydride and its derivatives, and fumaric acid and its derivatives. Derivatives of maleic anhydride are compounds that have an ethylenic double bond and a polar group such as a carboxyl group or an acid anhydride group within the same molecule. Specifically, examples include maleic acid, maleic acid monoester, maleic acid diester, maleimide and its N-substituted derivatives (e.g., N-substituted maleimide, maleic acid monoamide, maleic acid diamide, etc.), ammonium salts of maleic acid, metal salts of maleic acid, acrylic acid, methacrylic acid, methacrylic acid esters, glycidyl methacrylate, etc. Specific examples of fumaric acid derivatives include fumaric acid diester, metal salt of fumarate, ammonium salt of fumarate, and fumaric acid halides. Among these, fumaric acid or maleic anhydride are particularly preferred.

[0048] As the polyarylene ether modified with a functional group, dicarboxylic acid-modified polyarylene ether is preferable, and fumaric acid-modified polyarylene ether or maleic acid-modified polyarylene ether is more preferable. Specifically, (styrene-maleic anhydride)-polyphenylene ether-graft polymer, maleic anhydride-modified polyphenylene ether, fumaric acid-modified polyphenylene ether, glycidyl methacrylate-modified polyphenylene ether, amine-modified polyphenylene ether and other modified polyphenylene ether-based polymers can be mentioned. Among them, modified polyphenylene ether is preferable, maleic anhydride-modified polyphenylene ether or fumaric acid-modified polyphenylene ether is more preferable, and fumaric acid-modified polyphenylene ether is particularly preferable.

[0049] The degree of modification (modification degree or modification amount) of the polyarylene ether modified with a functional group can be determined by infrared (IR) absorption spectroscopy or titration method. When determining the degree of modification from infrared (IR) absorption spectroscopy, it can be determined from the intensity ratio of the peak intensity indicating the absorption of the compound used as the modifier and the peak intensity of the spectrum indicating the absorption of the corresponding polyarylene ether. For example, in the case of fumaric acid-modified polyphenylene ether, the peak intensity (A) at 1790 cm indicating the absorption of fumaric acid and the peak intensity of 1704 cm indicating the absorption of polyphenylene ether (PPE) -1 The ratio (B) is used to obtain the formula: degree of modification = (A) / (B). The degree of modification of the polyarylene ether modified with a functional group is preferably 0.05 to -1 -1 20.

[0050] When determining the modification amount by titration, it can be determined as the acid content from the neutralization titration amount measured in accordance with JIS K 0070-1992. The modification amount of the polyarylene ether modified with a functional group is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, still more preferably 1.0 to 10% by mass, and particularly preferably 1.0 to 5.0% by mass based on the mass of the polyarylene ether.

[0051] Polyarylene ethers modified with functional groups can be prepared, for example, by reacting polyarylene ether with various modifying agents in the presence or absence of a radical generator, optionally in the presence of a solvent or other resin. Known modification methods include solution modification and melt modification.

[0052] When using fumaric acid or its derivatives as a modifying agent, fumaric acid-modified polyarylene ether can be obtained by reacting polyarylene ether with fumaric acid or its derivatives in the presence or absence of a radical generator, optionally in the presence of an aromatic hydrocarbon solvent and other resins. The aromatic hydrocarbon solvent is not particularly limited and can dissolve the polyarylene ether, fumaric acid or its derivatives, and optionally used radical generators, and is inert to the generated radicals. Specifically, suitable examples include benzene, toluene, ethylbenzene, xylene, chlorobenzene, and tert-butylbenzene. Among these, it is preferable to use benzene, toluene, chlorobenzene, and tert-butylbenzene, which have small chain transfer constants. The solvent may be used alone or in a mixture of two or more. There are no particular restrictions on the proportion of aromatic hydrocarbon solvent used, and it should be selected appropriately depending on the situation. Generally, it should be set in the range of 1 to 20 times (mass ratio) relative to the polyarylene ether used.

[0053] The proportion of fumaric acid or its derivative used as a denaturing agent is preferably 1 to 20 parts by mass, more preferably 3 to 15 parts by mass, per 100 parts by mass of polyarylene ether. A sufficient amount of denaturation (degree of denaturation) can be obtained with 1 part by mass or more. If the amount is 20 parts by mass or less, post-processing such as purification after denaturation can be carried out appropriately.

[0054] The radical generator used in the solution modification of polyarylene ether is not particularly limited. It is preferable to use a radical generator that has a decomposition temperature suitable for the reaction temperature and has a large hydrogen abstraction ability to effectively graft the modification agent onto the polyarylene ether. Specifically, examples include di-tert-butyl peroxide, dicumyl peroxide, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, benzoyl peroxide, decanoyl peroxide, etc. The proportion of radical generator used is preferably 15 parts by mass or less per 100 parts by mass of polyarylene ether. It is preferable that the radical generator is 15 parts by mass or less, as it is less likely to produce insoluble components. If the modification is carried out in the absence of a radical generator, a polyarylene ether with a low degree of modification (for example, a modification amount of 0.3 to 0.5% by mass) can be obtained.

[0055] When modifying polyarylene ethers in solution, specifically, the polyarylene ether and a modifying agent such as fumaric acid or its derivative are dissolved in an aromatic hydrocarbon solvent until homogeneous. If a radical generator is used, the radical generator is added at a temperature such that its half-life is 1 hour or less, and the reaction is carried out at that temperature. Temperatures where the half-life of the radical generator used exceeds 1 hour are undesirable because they require a long reaction time. The reaction time can be selected as appropriate, but in order to allow the radical generator to act effectively, it is preferable to carry out a time-degradation reaction at a predetermined reaction temperature for a duration of at least three times the half-life of the radical generator. After the reaction is complete, the reaction solution is added to a poor solvent for polyarylene ether, such as methanol, and the precipitated modified polyarylene ether is recovered and dried to obtain the desired functionally modified polyarylene ether.

[0056] When modifying polyarylene ether by melt, a functionally modified polyarylene ether can be obtained by melt-kneading the polyarylene ether with a modifying agent, such as fumaric acid or its derivative, using an extruder, with or without a radical generating agent. The proportion of fumaric acid or its derivative used is preferably 1 to 5 parts by mass, more preferably 2 to 4 parts by mass, per 100 parts by mass of polyarylene ether. If it is 1 part by mass or more, a sufficient amount of modification (degree of modification) is achieved, and if it is 5 parts by mass or less, the modification efficiency of fumaric acid or its derivative can be kept good, and the amount of fumaric acid etc. remaining in the pellet can be suppressed.

[0057] The radical generating agent used for the melt modification of polyarylene ethers is preferably one that exhibits a half-life of 1 minute at a temperature of 300°C or higher. Radical generating agents with a half-life of 1 minute at a temperature below 300°C, such as peroxides and azo compounds, do not sufficiently modify the polyarylene ether. Examples of radical generators include 2,3-dimethyl-2,3-diphenylbutane, 2,3-diethyl-2,3-diphenylbutane, 2,3-diethyl-2,3-diphenylhexane, and 2,3-dimethyl-2,3-di(p-methylphenyl)butane. Among these, 2,3-dimethyl-2,3-diphenylbutane, which exhibits a half-life of 1 minute at a temperature of 330°C, is preferably used. The proportion of radical generator used is preferably selected in the range of 0.1 to 3 parts by mass, more preferably 0.5 to 2 parts by mass, per 100 parts by mass of polyarylene ether. A high modification effect can be obtained if the amount is 0.1 parts by mass or more, and if it is 3 parts by mass or less, the polyarylene ether can be efficiently modified and insoluble components are less likely to be generated.

[0058] One method for melt-modifying polyarylene ether is to uniformly dry-blend polyarylene ether, fumaric acid or its derivative, and a radical generator at room temperature, and then carry out a melt reaction in the range of 300-350°C, which is substantially the mixing temperature of polyarylene ether. At temperatures above 300°C, the melt viscosity can be appropriately maintained, and at temperatures below 350°C, the decomposition of polyarylene ether can be suppressed.

[0059] In the case of the fumaric acid-modified polyarylene ether, which is a particularly preferred type of polyarylene ether modified with functional groups by the method described in detail above, the amount of modification (modifier content) determined by the titration method described above is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, even more preferably 1 to 10% by mass, and particularly preferably 1.0 to 5.0% by mass. If the amount of modification is 0.1% by mass or more, a polyarylene ether with sufficient mechanical properties and heat resistance can be obtained. A modification amount of 20% by mass or less is sufficient.

[0060] The amount of thermoplastic resin (C) added is preferably 3 to 15 parts by mass per 100 parts by mass of the total of thermoplastic resins (A), (B), and (C). More preferably, it is 5 to 12 parts by mass, and even more preferably 7 to 10 parts by mass.

[0061] In the thermoplastic resin composition of this embodiment, the mass ratio of thermoplastic resin (A) to the total mass of thermoplastic resin (B) and thermoplastic resin (C) [(A):((B)+(C))] is preferably 40:60 to 60:40. More preferably, it is 45:55 to 55:45. By setting the ratio within this range, the cross-section of the thermoplastic resin composition is more likely to have the morphology described above.

[0062] The thermoplastic resin composition of this embodiment may contain the above-mentioned thermoplastic resins (A) to (C) and have a predetermined morphology, but is not particularly limited to other materials. Known fillers and additives such as reinforcing fibers, rubbery elastic materials, antioxidants, crosslinking agents, crosslinking aids, nucleating agents, mold release agents, plasticizers, compatibilizers, colorants, and antistatic agents can be used as long as they do not hinder the objective of the present invention.

[0063] In the thermoplastic resin composition of this embodiment, the content of thermoplastic resins (A) to (C) relative to the total resin components (thermoplastic resin, rubbery elastic body) may be 80% by mass or more, 90% by mass or more, or 95% by mass or more. In one embodiment, the resin components (thermoplastic resin, rubbery elastic body) may consist substantially only of thermoplastic resins (A) to (C). In this case, unavoidable impurities may be present. The following are examples of components other than the thermoplastic resins (A) to (C) mentioned above.

[0064] <Reinforced fiber (D)> Examples of reinforcing fibers (D) include glass fibers and carbon fibers, with carbon fibers being preferred. Various types of carbon fibers can be used, including PAN-based carbon fibers made from polyacrylonitrile, pitch-based carbon fibers made from coal tar pitch found in petroleum and coal, and phenol-based carbon fibers made from thermosetting resins, such as phenolic resins. The carbon fiber may be obtained by vapor deposition or may be recycled carbon fiber (RCF). Thus, the carbon fiber is not particularly limited, but it is preferable that it be at least one type of carbon fiber selected from the group consisting of PAN-based carbon fiber, pitch-based carbon fiber, thermosetting carbon fiber, phenol-based carbon fiber, vapor-deposited carbon fiber, and recycled carbon fiber (RCF).

[0065] Carbon fibers vary in degree of graphitization depending on the raw material quality and firing temperature during manufacturing, but they can be used regardless of the degree of graphitization. The shape of the carbon fiber is not particularly limited, and carbon fibers having at least one shape selected from the group consisting of milled fibers, chopped strands, short fibers, rovings, filaments, tows, whiskers, nanotubes, etc., can be used. In the case of chopped strands, those with an average fiber length of 0.1 to 50 mm and an average fiber diameter of 5 to 20 μm are preferably used. The density of carbon fibers is not particularly limited, but is generally between 1.75 and 1.95 g / cm³. 3 Those that are preferable.

[0066] The carbon fibers may be in the form of single fibers, fiber bundles, or a mixture of both. The number of single fibers constituting each fiber bundle may be approximately uniform or different. The average fiber diameter of the carbon fibers varies depending on the form, but for example, carbon fibers with an average fiber diameter of preferably 0.0004 to 15 μm, more preferably 3 to 15 μm, and even more preferably 5 to 10 μm can be used.

[0067] When the carbon fiber-containing component is a woven fabric, nonwoven fabric, or unidirectional material, single fibers with an average fiber diameter of preferably 3 to 15 μm, more preferably 5 to 7 μm, can be used. Furthermore, when the carbon fiber-containing component is in the form of a woven fabric, nonwoven fabric, or unidirectional material, bundles of carbon fibers in one direction (fiber bundles) can be used. For such carbon fiber-containing components, products consisting of bundles of 6,000 (6K), 12,000 (12K), 24,000 (24K), or 60,000 (60K) single carbon fibers supplied by a carbon fiber manufacturer can be used as is, or these bundles can be further bundled. The fiber bundle may be untwisted, twisted, or untwisted. The fiber bundle may be included in the molded body in an opened state, or it may be included as a fiber bundle without being opened. If the carbon fiber-containing component is a woven fabric, nonwoven fabric, or unidirectional material, a molded body can be obtained by immersing the component in thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C).

[0068] Components containing carbon fibers, especially woven fabrics, nonwoven fabrics, and unidirectional materials, are preferably thin. From the viewpoint of obtaining a thin carbon fiber composite material, the thickness of the carbon fiber component is preferably 3 mm or less. In particular, for unidirectional materials, a thickness of 0.2 mm or less is preferable. There is no particular lower limit to the thickness of the carbon fiber component, but it is often 7 μm or more, and from the viewpoint of quality stability, it is 10 μm or more, more preferably 20 μm or more.

[0069] Carbon fibers may have a sizing agent attached to their surface. When using carbon fibers with a sizing agent attached, the type of sizing agent can be appropriately selected depending on the type of carbon fiber and thermoplastic resin, and is not particularly limited. Various types of carbon fibers are available, such as those treated with epoxy sizing agents, urethane sizing agents, polyamide sizing agents, or those without a sizing agent, but in the present invention, they can be used regardless of the type or presence of the sizing agent.

[0070] The thermoplastic resin composition of the present invention contains reinforcing fibers (D) in an amount of preferably 1 to 500 parts by mass, more preferably 1 to 400 parts by mass, even more preferably 1 to 350 parts by mass, even more preferably 1 to 200 parts by mass, even more preferably 1 to 100 parts by mass, and even more preferably 1 to 50 parts by mass, per 100 parts by mass of the total of thermoplastic resins (A), thermoplastic resin (B), and thermoplastic resin (C). Furthermore, to obtain excellent strength, it is preferable to include 15 parts by mass or more, and even more preferably 20 parts by mass or more. If the amount of carbon fibers is within the above range, the molded article of the present invention will have excellent mechanical strength.

[0071] Preferably, the surface of the reinforcing fiber (D) is coated with the first phase, rather than the second phase, of the two phases that form a co-continuous morphology. This improves adhesion with the reinforcing fiber (D) and allows the molded product to exhibit excellent mechanical strength.

[0072] In one embodiment, the thermoplastic resin composition preferably contains reinforcing fibers (D). This increases the mechanical strength of the molded article. Furthermore, a molded article can be obtained in which the strength retention rate after moist heat treatment at 80°C / 95%RH for 500 hours, represented by the following formula (1), is 80% or more.

number

[0073] <Other> The following rubber-like elastic materials can be added, to the extent that they do not affect the structure and effects of the present invention. Various materials can be used as rubber-like elastic materials. For example, natural rubber, polybutadiene, polyisoprene, polyisobutylene, chloroprene rubber, polysulfide rubber, thiocol rubber, acrylic rubber, urethane rubber, silicone rubber, epichlorohydrin rubber, styrene-butadiene block copolymer (SBR), hydrogenated styrene-butadiene block copolymer (SEB), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (SEP), styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-butadiene random copolymer, hydrogenated styrene-butadiene random copolymer, styrene-ethylene-propylene random copolymer, styrene-ethylene-butylene random copolymer, ethylene propylene rubber (EPR), and ethylene propylene diene rubber (EPDM). Examples include core-shell type particulate elastic materials such as acrylonitrile-butadiene-styrene-core-shell rubber (ABS), methyl methacrylate-butadiene-styrene-core-shell rubber (MBS), methyl methacrylate-butyl acrylate-styrene-core-shell rubber (MAS), octyl acrylate-butadiene-styrene-core-shell rubber (MABS), alkyl acrylate-butadiene-acrylonitrile-styrene-core-shell rubber (AABS), butadiene-styrene-core-shell rubber (SBR), and siloxane-containing core-shell rubber including methyl methacrylate-butyl acrylate siloxane, or rubbers modified from these. Among these, SBR, SBS, SEB, SEBS, SIR, SEP, SIS, SEPS, core-shell rubber, or modified rubbers thereof are particularly preferred.

[0074] Examples of modified rubber-like elastic materials include styrene-butyl acrylate copolymer rubber, styrene-butadiene block copolymer (SBR), hydrogenated styrene-butadiene block copolymer (SEB), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (SEP), styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), styrene-butadiene random copolymer, hydrogenated styrene-butadiene random copolymer, styrene-ethylene-propylene random copolymer, styrene-ethylene-butylene random copolymer, ethylene propylene rubber (EPR), ethylene propylene diene rubber (EPDM), etc., which have been modified with a modifying agent having polar groups.

[0075] In addition to reinforcing fibers (D), organic fillers can also be added as fillers. Examples of organic fillers include organic synthetic fibers and natural plant fibers. Specific examples of organic synthetic fibers include fully aromatic polyamide fibers and polyimide fibers. One type of organic filler may be used, or two or more types may be used in combination. The amount added is preferably 1 to 350 parts by mass, and more preferably 5 to 200 parts by mass, per 100 parts by mass of the total of thermoplastic resins (A), (B), and (C). If the amount is 1 part by mass or more, the effect of the filler is sufficiently obtained, and if it is 350 parts by mass or less, the dispersibility is not inferior and the moldability is not adversely affected.

[0076] While there are various antioxidants, phosphorus-based antioxidants such as monophosphites and diphosphites, including tris(2,4-di-tert-butylphenyl) phosphite and tris(mono and dinonylphenyl) phosphite, and phenol-based antioxidants are particularly preferred. As for diphosphites, the general formula [ka] (In the formula, R 30 and R 31 Each of these independently represents an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms. It is preferable to use a phosphorus-based compound represented by [formula].

[0077] Specific examples of phosphorus compounds represented by the above general formula include distearyl pentaerythritol diphosphite; dioctyl pentaerythritol diphosphite; diphenyl pentaerythritol diphosphite; bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite; bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite; and dicyclohexyl pentaerythritol diphosphite.

[0078] Known phenolic antioxidants can be used, and specific examples include 2,6-di-tert-butyl-4-methylphenol; 2,6-diphenyl-4-methoxyphenol; 2,2'-methylenebis(6-tert-butyl-4-methylphenol); 2,2'-methylenebis-(6-tert-butyl-4-methylphenol); 2,2'-methylenebis[4-methyl-6-(α-methylcyclohexyl)phenol]; 1,1-bis(5-tert-butyl-4-hydroxy-2-methylphenyl)butane; 2,2'-methylenebis(4-methyl-6-cyclohexylphenol); 2,2'-methylenebis(4-methyl-6-nonylphenol); 1,1,3-tris(5-tert-butyl-4-hydroxy-2-methylphenyl)butane; 2,2-bis(5-tert-butyl-4-hydroxy-2-methylphenyl) Examples include droxy-2-methylphenyl)-4-n-dodecylmercaptobutane; ethylene glycol-bis[3,3-bis(3-tert-butyl-4-hydroxyphenyl)butyrate]; 1,1-bis(3,5-dimethyl-2-hydroxyphenyl)-3-(n-dodecylthio)-butane; 4,4'-thiobis(6-tert-butyl-3-methylphenol); 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-2,4,6-trimethylbenzene; 2,2-bis(3,5-di-tert-butyl-4-hydroxybenzyl) malonate dioctadecyl ester; n-octadecyl-3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate; and tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane. In addition to the phosphorus-based and phenol-based antioxidants mentioned above, amine-based antioxidants, sulfur-based antioxidants, and other similar agents can be used individually or in combination.

[0079] The above antioxidant is usually in an amount of 0.005 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the total of the above thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C). If the blending ratio of the antioxidant is 0.005 parts by mass or more, the decrease in molecular weight of thermoplastic resin (A) or the thermoplastic resin can be suppressed. If it is 5 parts by mass or less, the mechanical strength can be maintained well. When multiple types of antioxidants are included in the composition as antioxidants, it is preferable to adjust the total amount so that it falls within the above range. The amount of antioxidant blended is more preferably 0.01 to 4 parts by mass, and even more preferably 0.02 to 3 parts by mass, per 100 parts by mass of resin (S), or per 100 parts by mass of the total of unmodified polyarylene ether and thermoplastic resin.

[0080] Preferably, the nucleating agent is one or more selected from the group consisting of inorganic crystallization nucleating agents and organic crystallization nucleating agents. Among these, organic crystallization nucleating agents are preferred. Examples of organic crystallization nucleating agents include alkali metal salts of organic carboxylic acids, alkaline earth metal salts of organic carboxylic acids, organic compounds of phosphoric acid or phosphorous acid and their metal salts, phthalocyanine derivatives, sorbitol derivatives, and the like.

[0081] More specifically, for example, aluminum di(p-tert-butylbenzoate), sodium salt of benzoic acid, hydroxyaluminum salt of p-tert-butylbenzoate, metal salts of carboxylic acids including hydroxy-di(p-tert-butylbenzoate)aluminum, sodium methylenebis(2,4-di-tert-butylphenol) phosphate, sodium-2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate, lithium [2,2'-methylenebis(4,6-di-tert-butylphenyl)]] phosphate, potassium [2,2'-methylenebis(4,6-di-tert-butylphenyl)]] phosphate, sodium bis(4-tert-butylphenyl) phosphate, sodium methylene(2,4-tert-butylphenyl) phosphate, aluminum=bis(4,6',6,6'-tetra-tert-butyl-2,2' Metal salts of phosphoric acid, such as methylenediphenyl(phosphate) hydroxide, and [[2,2'-methylenebis(4,6-di-tert-butylphenyl)]]ammonium phosphate, can be arbitrarily selected from known sources. Complexes containing these can also be used.

[0082] The amount of nucleating agent is not particularly limited, but is preferably 0.01 to 5 parts by mass, more preferably 0.04 to 2 parts by mass, per 100 parts by mass of the total of thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C).

[0083] As a release agent, any known one such as polyethylene wax, silicone oil, long-chain carboxylic acid, or long-chain carboxylic acid metal salt can be arbitrarily selected and used. These release agents can be used individually or in combination of two or more. The amount of release agent is not particularly limited, but is preferably 0.1 to 3 parts by mass, more preferably 0.2 to 1 part by mass, per 100 parts by mass of the total of the thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C).

[0084] <Method for manufacturing molded articles> In one embodiment of the present invention, the thermoplastic resin composition is a molded article. The molded article can be formed into a desired shape by, for example, putting the above-mentioned thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C), along with optionally reinforcing fibers (D) and additives, into a molding machine (extrusion molding machine, injection molding machine, etc.), melting and kneading them in the molding machine, and then shaping them with a mold. Powders, pellets, etc., which are obtained by melting and kneading some or all of the components of a thermoplastic resin composition and then granulating them, may be fed into the molding machine.

[0085] In one embodiment, a molded article can also be formed by a method that includes the steps of producing an intermediate product of a thermoplastic resin composition containing thermoplastic resin (B) and thermoplastic resin (C), and adding thermoplastic resin (A) to the intermediate product. Alternatively, a molded article can be manufactured by immersing reinforcing fibers (D) in a thermoplastic resin composition containing thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C). When using this method, the form of the reinforcing fibers (D) can be at least one form selected from chopped strands, woven fabrics, nonwoven fabrics, or unidirectional materials.

[0086] Furthermore, a molded article can also be formed by a method that includes the steps of: producing a reinforcing fiber member containing a thermoplastic resin (A) and reinforcing fibers (D); and adding a thermoplastic resin composition containing a thermoplastic resin (A), a thermoplastic resin (B), and a thermoplastic resin (C) to the reinforcing fiber member.

[0087] The means for producing a reinforced fiber member comprising a thermoplastic resin (A) and reinforcing fibers (D) are not particularly limited. For example, methods include immersing the reinforcing fibers (D) in a thermoplastic resin (A) under a suitable solvent, applying a mixture of thermoplastic resin (A) and a suitable vehicle to the reinforcing fibers, and adding a mixture of thermoplastic resin (A) and a sizing material to the reinforcing fibers (D). When using this method, the form of the reinforcing fiber (D) can be at least one form selected from chopped strands, woven fabrics, nonwoven fabrics, or unidirectional materials.

[0088] Furthermore, a molded article can also be formed by a method that includes the steps of: producing a reinforcing fiber member containing a thermoplastic resin (C) and reinforcing fibers (D); and adding a thermoplastic resin composition containing a thermoplastic resin (A), a thermoplastic resin (B), and a thermoplastic resin (C) to the reinforcing fiber member. The means for producing a reinforced fiber member comprising a thermoplastic resin (C) and reinforcing fibers (D) can be the same as those for a reinforced fiber member comprising a thermoplastic resin (A) and reinforcing fibers (D). The form of the reinforcing fibers (D) used can also be the same.

[0089] In a subsequent step, a thermoplastic resin composition containing thermoplastic resin (A), thermoplastic resin (B), and thermoplastic resin (C) is added to a reinforcing fiber member containing thermoplastic resin (A) and reinforcing fiber (D) obtained in the above step. The method of adding the thermoplastic resin composition to the reinforcing fiber member is not limited, and the thermoplastic resin composition may be in a solution state or a molten state. Specifically, examples include immersing the reinforcing fiber member in the thermoplastic resin composition under a suitable solvent, laminating a film containing the thermoplastic resin composition and performing a melt press, and directly adding the powder of the thermoplastic resin composition to the reinforcing fiber member and then melting it.

[0090] The reinforcing fiber member may contain a thermoplastic resin (A) and reinforcing fibers (D) or a thermoplastic resin (C) and reinforcing fibers (D). The thermoplastic resin composition may be added in the form of a woven fabric, nonwoven fabric, or unidirectional material. Alternatively, the reinforcing fiber member, which has the form of a woven fabric or the like, may be cut into short pieces to form a chopped material, after which the thermoplastic resin composition may be added. After adding the thermoplastic resin composition to the reinforcing fiber member, a molded article can be manufactured by various molding methods described later.

[0091] The shape of the molded article is not particularly limited and can include, for example, sheets, films, fibers, textiles, nonwoven fabrics, containers, injection-molded articles, blow-molded articles, press-molded articles, etc. Depending on the form of the reinforcing fibers used, the molded article may also include a unidirectional fiber reinforcing material, or at least one component selected from textile-like reinforcing fibers and nonwoven-like reinforcing fibers. Multiple such molded articles can be laminated to form a laminate. This laminate is also included in the term "molded article" in this specification.

[0092] A molded article containing at least one component selected from the group consisting of unidirectional fiber reinforcement, woven reinforcing fibers, and nonwoven reinforcing fibers has high mechanical strength. For example, it has a mechanical strength of 250 MPa or more, more preferably 300 MPa or more, when measured in accordance with ISO 178:2010, with a support distance of 4 cm, a test speed of 2 mm / min, and a temperature of 23°C.

[0093] The molded articles of the present invention are suitable as industrial materials such as electrical and electronic materials (connectors, printed circuit boards, etc.), industrial structural materials, automotive parts (vehicle-mounted connectors, wheel caps, cylinder head covers, etc.), home appliances, various machine parts, pipes, sheets, trays, films, etc.

[0094] Specifically, the molded articles of the present invention, as thermoplastic carbon fiber reinforced plastics (CFRTPs), can be applied to a wide range of applications, including automobiles, aircraft, and sporting goods, where further weight reduction is required. These molded articles can also be applied to improve engineering plastics, which require resistance to high-load environments such as high loads and high temperatures. Molded articles containing the resin composition of the present invention have short molding times, excellent recyclability, easy resin immersion during molding, and sufficient mechanical strength, making them practical for a wide range of applications.

[0095] Specifically, applications include automotive, motorcycle / bicycle, water heater and eco-friendly water heater-related applications, home appliance / electronic equipment applications, building materials applications, and daily necessities applications. Examples of automotive applications include sliding parts such as gears, automotive panel components, millimeter-wave radomes, IGBT housings, radiator grilles, meter hoods, fender supports, front engine covers, front strut tower panels, transmission center tunnels, radiator core supports, front dashes, door interiors, rear luggage back panels, rear luggage side panels, rear luggage floors, rear luggage partitions, roofs, door frame pillars, seat backs, headrest supports, engine components, crash boxes, front floor tunnels, front floor panels, undercovers, undersupport rods, impact beams, front cowls, and front strut tower bars.

[0096] The molded articles of the present invention can suitably constitute, for example, power electronic units, rapid charging plugs, in-car chargers, lithium-ion batteries, battery control units, power electronic control units, three-phase synchronous motors, home charging plugs, and the like.

[0097] Furthermore, the solar twilight sensor, alternator, EDU (Electronic Injector Driver Unit), electronic throttle, tumble control valve, throttle position sensor, radiator fan controller, stick coil, A / C pipe joint, diesel particulate filter, headlight reflector, charge air duct, charge air cooling head, intake air temperature sensor, gasoline fuel pressure sensor, cam / crank position sensor, combination valve, engine oil pressure sensor, transmission gear angle sensor, continuously variable transmission oil pressure sensor, ELCM (Evaporic Check Module) pump, water pump impeller, steering roll connector, ECU (Engine Computer Unit) connector, ABS (Anti-lock Braking System) reservoir piston, actuator cover, etc., can be suitably configured.

[0098] A molded article containing the thermoplastic resin composition of the present invention can also be suitably used, for example, as a sealing material for sealing sensors in an in-vehicle sensor module. The sensors are not particularly limited and can include, specifically, atmospheric pressure sensors (for example, altitude compensation), boost pressure sensors (for example, fuel injection control), integrated atmospheric pressure sensors, acceleration sensors (for example, airbags), gauge pressure sensors (for example, seat condition control), tank pressure sensors (for example, fuel tank leak detection), refrigerant pressure sensors (for example, air conditioning control), coil drivers (for example, ignition coil control), EGR (exhaust gas recirculation) valve sensors, airflow sensors (for example, fuel injection control), intake manifold pressure (MAP) sensors (for example, fuel injection control), oil pans, radiator caps, intake manifolds, and the like.

[0099] Molded articles containing the thermoplastic resin composition of the present invention are not limited to the automotive parts exemplified above, but are also suitably used in, for example, high-voltage (harness) connectors, millimeter-wave radomes, IGBT (insulated gate bipolar transistor) housings, battery fuse terminals, radiator grilles, meter hoods, inverter cooling water pumps, battery monitoring units, structural components, intake manifolds, high-voltage connectors, motor control ECUs (engine computer units), inverters, piping components, canister purge valves, power units, busbars, motor reducers, canisters, and the like. Furthermore, it is suitably used in motorcycle and bicycle parts, more specifically in motorcycle components, motorcycle fairings, and bicycle components. Examples of motorcycle / bicycle applications include motorcycle components, motorcycle fairings, and bicycle components.

[0100] Molded articles containing the resin composition of the present invention also exhibit excellent chemical resistance and can therefore be used in various electrical appliances. For example, they are preferably used to form components of water heaters, specifically natural refrigerant heat pump water heaters known as "EcoCute" (registered trademark). Examples of such components include shower parts, pump parts, and piping parts. More specifically, examples include single-port circulation connection fittings, relief valves, mixing valve units, heat-resistant traps, pump casings, composite water valves, water inlet fittings, resin joints, piping parts, resin pressure reducing valves, and water tap elbows.

[0101] Molded articles containing the resin composition of the present invention are suitably used in home appliances and electronic devices, and more specifically, can be used as components in telephones, mobile phones, microwave ovens, refrigerators, vacuum cleaners, office automation equipment, power tool parts, electrical components, antistatic applications, high-frequency electronic components, high-heat-dissipation electronic components, high-voltage components, electromagnetic shielding components, communication equipment products, AV equipment, personal computers, cash registers, electric fans, ventilation fans, sewing machines, ink peripheral components, ribbon cassettes, air cleaner components, heated toilet seat components, toilet seats, toilet lids, rice cooker components, optical pickup equipment, lighting fixture components, DVDs, DVD-RAMs, DVD pickup components, DVD pickup boards, switch components, sockets, displays, video cameras, filaments, plugs, high-speed color copiers (laser printers), inverters, air conditioners, keyboards, converters, televisions, facsimile machines, optical connectors, semiconductor chips, LED components, washing machine / washer-dryer components, dishwasher / dish-dryer components, and other similar products. Molded articles containing the resin composition of the present invention are also suitably used in building materials, and more specifically, examples include components such as exterior wall panels, back panels, partition wall panels, signal lights, emergency lights, and wall materials.

[0102] Molded articles containing the resin composition of the present invention are suitable for use in general merchandise, daily necessities, and more specifically, include chopsticks, lunch boxes, tableware containers, food trays, food packaging materials, aquariums, tanks, toys, sporting goods, surfboards, door caps, door steps, pachinko machine parts, remote-controlled cars, remote-controlled cases, stationery, musical instruments, tumblers, dumbbells, helmet box products, shutter blade components used in cameras, racket components for table tennis and tennis, and board components for skis and snowboards. Each of the various components described above may be made of a molded article that contains, in part or in whole, the thermoplastic resin composition of the present invention. [Examples]

[0103] The present invention will be described in detail below based on examples. The present invention is not limited to these examples. The constituent materials used in the examples are as follows. [Thermoplastic resin] (A-1): Polyamide 6 (manufactured by Ube Industries, Ltd.: 1022B) (B-1): Syndiotactic polystyrene (SPS, manufactured by Idemitsu Kosan Co., Ltd., racemicentad: 98%, MFR: 28g / 10min, melting point: 270℃) (C-1): Fumarate-modified polyphenylene ether (manufactured by Idemitsu Kosan Co., Ltd., produced by melt modification, modification amount 1.7% by mass, glass transition temperature 220°C) (C-2): Polyphenylene ether (SABIC: PX-100L) [Reinforced fiber] (D-1): Chopped carbon fiber (manufactured by Mitsubishi Chemical Corporation: TR066AB4E)

[0104] The resin melt flow rate (MFR) was measured in accordance with JIS K 7210-1:2014 (ISO 1133-1:2011) at a measurement temperature of 300°C and a load of 1.2 kg.

[0105] Example 1 100 parts by mass of a thermoplastic resin composition consisting of 50 parts by mass of polyamide 6(A-1), 40 parts by mass of SPS(B-1), and 10 parts by mass of fumaric acid-modified polyphenylene ether(C-1) was dry-blended and supplied from the raw material supply port upstream of a twin-screw kneader. 35 parts by mass of carbon fiber (D-1) was side-fed from a second raw material supply port located between the midstream and downstream sections, and the mixture was kneaded to obtain a thermoplastic resin composition (pellets). A twin-screw kneader with a cylinder diameter of 11 mm (manufactured by Thermo Fisher Scientific, Process 11) was used. The L / D ratio of the twin-screw kneader is 40, and the first to third kneading zones are provided upstream, midstream, and downstream in the direction of raw material flow. A first vacuum vent is provided behind the midstream kneading zone, and a second vacuum vent is provided behind the downstream kneading zone. The screw rotation speed was set to 250 rpm, and the set temperature was 300°C, which is 30°C higher than the melting point of SPS.

[0106] Comparative Examples 1-5 A thermoplastic resin composition was prepared in the same manner as in Example 1, except that the type and composition of the thermoplastic resin were changed as shown in Table 1.

[0107] [evaluation] The obtained thermoplastic resin compositions were subjected to bending tests and evaluation of their heat and moisture resistance, and their morphology was observed. The evaluation results are shown in Table 1. <Mechanical properties test: Bending test> A thermoplastic resin composition (pellets) was injection molded using an injection molding machine (Thermo Fisher Scientific, MiniJetPro) under the conditions of a cylinder temperature of 300°C and a mold temperature of 150°C to obtain a bending test specimen (2 mm thick). The mold used was ISO 527-2-5A, manufactured by Thermo Fisher Scientific. The bending properties of the bending test specimens obtained as described above were measured in accordance with ISO 178:2010. Specifically, the bending strength (MPa) and bending modulus (GPa) were measured under the conditions of a support distance of 5 cm, a temperature of 23°C, and a bending speed of 3 mm / min. A higher value indicates better bending properties.

[0108] <Evaluation of heat and humidity resistance> The test specimens were exposed to a small environmental testing chamber (ESPEC SH-221) at 80°C and 95% RH for 500 hours (moist heat treatment). The bending strength (MPa) of the treated specimens was measured under the conditions described above. The strength retention rate for the bending strength after molding and the bending strength after moist heat treatment was determined using the following formula (1).

number

[0109] <Observation of Morphology> A sample approximately 1 cm square was cut from the thermoplastic resin composition (the bending test specimen described above) using a wheel saw (ISOMET4000 (BUEHLER)). The sample was placed in a φ32 mm resin fixing cup and fixed with epoxy resin (Epoxy cure J (BUEHLER)). The resin-immobilized sample was polished using abrasive paper with silicon carbide-fixed abrasive grains in a precision polishing device (EcoMetTM250 + AutMetTM250 (manufactured by BUEHLER)) to obtain a cross-section for observation. For the cross-section used for observation, staining was performed by immersion in a phosphotungstic acid solution for 30 minutes to provide contrast to the observed components. In addition, a 10 nm thick coating of osmium metal was formed using Neoc-AN (manufactured by Meiwa Forsis Co., Ltd.) to provide conductivity for electron microscopy observation.

[0110] (Observation of co-continuous structures) Using a scanning electron microscope (SEM, IT500HR, JEOL Ltd.), a backscattered electron image of the observation cross-section was acquired by magnifying the core portion of the molded product cross-section (the portion excluding the surface layer less than 20 μm deep, the central part of the cross-section, and the cross-section parallel to the flow direction of the resin composition) to 10,000 times under conditions of an acceleration voltage of 15 kV and a spot size of 50. Figure 1 shows a cross-sectional SEM image of the thermoplastic resin composition obtained in Example 1. Figure 1 confirms the presence of a co-continuous structure. After electron staining with phosphotungstic acid, polyamide 6 was selectively stained and observed as a white region during SEM observation. The black regions mainly consist of syndiotactic polystyrene and fumaric acid-modified polyphenylene ether. Figure 2 shows a cross-sectional SEM image of the thermoplastic resin composition obtained in Comparative Example 1. Figure 2 confirms that it has a sea-island structure.

[0111] (Observation of each phase constituting the co-continuous structure) Using a scanning electron microscope (SEM), the core portion of the molded product cross-section (excluding the surface layer less than 20 μm deep, the central part of the cross-section, and the cross-section parallel to the flow direction of the resin composition) was magnified 30,000 times under conditions of an acceleration voltage of 15 kV and a spot size of 50, and a backscattered electron image of the observation cross-section was acquired. Figure 3 is a magnified view of the SEM image of Figure 1 (Example 1). From Figure 3, it was confirmed that a compatible mixture of syndiotactic polystyrene and fumaric acid-modified polyphenylene ether is dispersed in the first phase forming a co-continuous structure, and polyamide 6 is dispersed in the second phase, both of which have a sea-island structure. Figure 4 is a magnified view of the SEM image (Comparative Example 1) from Figure 2. It was confirmed that no co-continuous structure was formed.

[0112] (Average diameter of island structures) For Example 1, from the backscattered electron images of 10 non-overlapping observation cross-sections obtained by observing each phase constituting the above-described co-continuous structure, 0.20 μm 2 The area of ​​each of the 100 island regions, each with the following area, was measured. For each island region, the equivalent diameter obtained by converting it to a circle with that area was calculated, and the particle diameter was determined. The average diameter was calculated by the arithmetic mean of the 100 particle diameters. As a result, it was confirmed that the average diameter of the island structure was 500 nm or less. For the comparative example, a co-continuous structure could not be obtained from the observation of the co-continuous structure described above, and therefore, each phase forming the co-continuous structure could not be observed.

[0113] (Reinforcement fiber coating phase) The SEM image, which included the cross-section of the reinforcing fibers, was observed and visually inspected. Figure 5 shows a cross-sectional SEM image of the carbon fibers in the thermoplastic resin composition obtained in Example 1. From Figure 5, it can be confirmed that the carbon fibers are coated by a first phase that forms a co-continuous structure. Figure 6 shows a cross-sectional SEM image of the carbon fibers in the thermoplastic resin composition obtained in Comparative Example 1. From Figure 6, it can be confirmed that the carbon fibers are covered with both sea-island and island structures.

[0114] [Table 1]

[0115] (A-1): Polyamide 6 (B-1): Syndiotactic polystyrene (C-1): Fumarate-modified polyphenylene ether (C-2): Polyphenylene ether (D-1): Chopped carbon fiber

[0116] Example 1 demonstrates that the molded article of the present invention possesses excellent mechanical properties. Furthermore, the molded article of the present invention exhibits suppressed deterioration of mechanical properties after moist heat treatment.

Claims

1. The thermoplastic resin (A), the thermoplastic resin (B), and the thermoplastic resin (C) are included, It has a bicontinuous structure morphology, the first phase of the co-continuous structure is mainly composed of the thermoplastic resin (A), and the second phase of the co-continuous structure is mainly composed of a mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C); In the first phase, a mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C) is dispersed in the thermoplastic resin (A), A thermoplastic resin composition, wherein in the second phase, the thermoplastic resin (A) is dispersed in a mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C).

2. the average diameter of the mixed phase of the thermoplastic resin (B) and the thermoplastic resin (C) present in the first phase is 500 nm or less; The thermoplastic resin composition according to claim 1, wherein the thermoplastic resin (A) present in the second phase has an average diameter of 500 nm or less.

3. The thermoplastic resin composition according to claim 1, wherein the thermoplastic resin (A) and the thermoplastic resin (C) have polar functional groups, and the thermoplastic resin (B) and the thermoplastic resin (C) are completely compatible with each other.

4. The thermoplastic resin composition according to claim 3, wherein the polar functional groups of the thermoplastic resin (A) and the thermoplastic resin (C) are carboxyl groups or amino groups.

5. The thermoplastic resin composition according to claim 1 , wherein the thermoplastic resin (A) and the thermoplastic resin (B) are crystalline resins.

6. The thermoplastic resin composition according to claim 1 , wherein the thermoplastic resin (C) is a polyarylene ether.

7. The thermoplastic resin composition according to claim 1 , wherein the thermoplastic resin (B) is a syndiotactic polystyrene.

8. The thermoplastic resin composition according to claim 1, wherein the mass ratio ((A):((B)+(C))) of the thermoplastic resin (A) to the total of the thermoplastic resin (B) and the thermoplastic resin (C) is 40:60 to 60:

40.

9. The thermoplastic resin composition according to claim 1, wherein the thermoplastic resin (C) is 3 to 15 parts by mass per 100 parts by mass of the total of the thermoplastic resin (A), the thermoplastic resin (B), and the thermoplastic resin (C) ((A) + (B) + (C)).

10. The thermoplastic resin composition according to claim 1, further comprising reinforcing fibers (D).

11. The thermoplastic resin composition according to claim 10, wherein the reinforcing fiber (D) is at least one type selected from glass fibers and carbon fibers.

12. The thermoplastic resin composition according to claim 10, wherein the surface of the reinforcing fiber (D) is covered with the first phase.

13. A molded article made of the thermoplastic resin composition according to any one of claims 1 to 9.

14. A molded article made of the thermoplastic resin composition according to any one of claims 10 to 12.

15. The molded article according to claim 14, which has a strength retention of 80% or more after wet heat treatment at 80° C. / 95% RH for 500 hours, as represented by the following formula (1): [0045]